Optimalisasi Website Lembaga Belajar PIEP Menggunakan Adsense dan Konten untuk Menarik Minat Calon Siswa - Abidatul Izzah; Yohan Bakhtiar; Agustono Heriadi; Kunti Eliyen; Ellya Nurfarida (Universitas Medan Area, 2023)
The Permana International English Program (PIEP) is one of the learning institutions in the city of Pare, Kediri which was just established in 2021. The pandemic condition due to the Covid19 virus has hampered the institution's promotional activities. The existence of a website and social media can be used as a means of marketing. Managing the content of a website can give customers trust, make the agency look more professional, and can attract new customers. This community service activity aims to provide website management training and help produce more interesting website content. The stages carried out in this community service activity are conducting discussions with partners, helping to prepare interesting website content, and conducting content management training for PIEP as partners. The results of service activities are in the form of developing a website for PIEP that can be accessed from anywhere and has interesting content. The website that has been developed has been tested and can run well. It also been advertised using the Google Ads service. Website Traffic visitor shows an increase in visits during one month of installation on Google Ads.